Complete Genome Sequence of the Hippuricase-Positive Campylobacter avium Type Strain LMG 24591 - Miller, William G. (Genome Announc, 2017)
Campylobacter avium is a thermotolerant Campylobacter species that has been isolated from poultry. C. avium was also the second hippuricase-positive species to be identified within Campylobacter. Here, we present the genome sequence of the C. avium type strain LMG 24591 (=CCUG 56292(T)), isolated in 2006 from a broiler chicken in Italy.